1992
DOI: 10.1002/1097-0142(19921215)70:12<2861::aid-cncr2820701224>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns of prostate cancer mortality. Evidence for a protective effect of ultraviolet radiation

Abstract: Background. Prostate cancer is the most prevalent nonskin cancer among men in the United States and is the second leading cause of cancer deaths in men, The cause of prostate cancer remains obscure. Recently it was hypothesized that low levels of vitamin D, a hormone with potent antitumor properties, may increase the risk for clinical prostate cancer. Methods. Because the major source of vitamin D is casual exposure to ultraviolet (UV) radiation, the authors examined the geographic distributions of UV radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
0
10

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(258 citation statements)
references
References 32 publications
12
236
0
10
Order By: Relevance
“…Our suggestion of a relationship between the calcidiol level and cancer prognosis is supported by a number of publications showing a north -south gradient of cancer incidence and/or death rates in many countries in the northern hemisphere Gorham et al, 1990;Hanchette and Schwartz, 1992;John et al, 1999;Grant, 2002Grant, , 2004Grant and Garland, 2004;Tuohimaa et al, 2004). Practically all investigators are of the opinion that this gradient is related to sun-induced vitamin D 3 in skin.…”
supporting
confidence: 61%
“…Our suggestion of a relationship between the calcidiol level and cancer prognosis is supported by a number of publications showing a north -south gradient of cancer incidence and/or death rates in many countries in the northern hemisphere Gorham et al, 1990;Hanchette and Schwartz, 1992;John et al, 1999;Grant, 2002Grant, , 2004Grant and Garland, 2004;Tuohimaa et al, 2004). Practically all investigators are of the opinion that this gradient is related to sun-induced vitamin D 3 in skin.…”
supporting
confidence: 61%
“…In ecological studies of populations and sunlight exposure (no individual data) sunlight has been found to have a protective effect for prostate cancer [136], ovarian cancer [137], and breast cancer [138]. Recently Grant found that sunlight was also protective for bladder, endometrial, renal cancer, multiple myeloma, and Non-Hodgkins lymphoma in Europe [139] and bladder, esophageal, kidney, lung, pancreatic, rectal, stomach, and corpus uteri cancer in the USA [140].…”
Section: Reviewmentioning
confidence: 99%
“…Thus, it was concluded that UVB had a protective effect against development of prostate cancer. 28 In 1992, Hanchette and Schwartz 22 proposed that sunlight and vitamin D may play a role in prostate cancer. Mortality rates in the United States from prostate cancer showed a negative correlation with UVB exposure.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…21 Both body mass index and lean body mass were positively associated with the risk of prostate cancer and were more strongly related to mortality than to incidence. Other factors that influence the occurrence of the disease are dietary habits (diet that includes a high intake of fat, meat and dairy products), 22,23 pattern of sexual behavior, alcohol consumption, 24 exposure to ultraviolet radiation, 22,[25][26][27][28] occupational exposure 29 and familial genetic inheritance. 5,[30][31][32][33][34][35] Finally, factors such as smoking, 36 vasectomy 37 and physical activity 38 have been investigated in several studies, but the general consensus is that they do not affect risk of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%